Phytochemical investigation and nephroprotective potential of Sida cordata in rat - Shah, Naseer Ali (BMC Complement Altern Med, 2017)
BACKGROUND: Plants are an efficient source of natural antioxidant against free radicals causing kidney damages. Sida cordata ethyl acetate fraction has been reported for strong in vitro antioxidant potency, previously. In the present study, our objective was to evaluate its in vivo antioxidant potency against CCl(4) induced nephrotoxicity and investigates the bioactive phytochemicals by HPLC-DAD analysis. METHODS: Phytochemical analysis was performed by HPLC-DAD methodology. For in vivo study, 42 male Sprague-Dawley rats were treated with alternatively managed doses for 60 days. Group I animals were remained untreated. Group II animals were treated with vehicle (1 mL of olive oil) by intragastric route on alternate days. Group III was treated with 30% CCl(4) (1 mL/kg b.w.) i.p. Group IV was treated with 30% CCl(4) (1 mL/kg b.w.) i.p and silymarin intragastric. Group V and VI rats were treated with 30% CCl(4) and SCEE (150 and 300 mg/kg b.w., respectively) intragastric. Group VII animals were treated with SCEE (300 mg/kg b.w.) intragastrically. Blood parameters, Serum proteins and urine profile were investigated. Activities of tissue enzyme i.e. catalase, peroxidase, superoxide dismutase, glutathione-S-transferase, glutathione reductase, GSH and γ-GT were evaluated. Histopathological observations, total protein contents, lipid peroxidation, DNA damage and relative weight were also analyzed. RESULTS: Gallic acid, catechin and caffeic acid were identified in SCEE fraction by HPLC-DAD. Decrease in the count of red blood cells, neutrophils, eosinophils and concentration of hemoglobin whereas increase in lymphocyte count and estimation of sedimentation rate (ESR) with 1 mL CCl(4) (30% in Olive oil) administration (30 doses in 60 days) was restored dose dependently with co-treatment of SCEE (150 and 300 mg/kg b.w.). Treatment of rats with CCl(4) markedly (P < 0.01) increased the count of urinary red blood cells and leucocytes, concentration of urea, creatinine and urobilinogen and specific gravity whereas creatinine clearance was reduced. Serum level of total protein, albumin, globulin, nitrite, creatinine and blood urea nitrogen (BUN) was significantly increased (P < 0.01) by CCl(4) treatment. The activity of antioxidant enzymes; catalase, superoxide dismutase, glutathione peroxidase, glutathione-S-transferase and glutathione reductase and content of reduced glutathione was decreased (P < 0.01) significantly. However, increased concentration (P < 0.01) of thiobarbituric acid reactive substances and histopathological injuries were noticed in the renal tissues of rats after the treatment with CCl(4). Co-administration of SCEE, dose dependently, protected the alterations in the studied parameters of rats at 150 and 300 mg/kg b.w. The present study revealed that SCEE could be used as a possible remedy for renal toxicity abnormalities. CONCLUSION: These results are an evidence of the renal protective role of S.cordat ethyl acetate fraction against CCl(4) induced nephrotoxicity in rats which may be due to its antioxidant compounds.